Utilisation of the Performance of the State Civil Apparatus - Hartini Jatmikowati, Sri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyse and describe the utilization of performance of the state civil apparatus in the regional secretariat of Malang Regency. This type of research is descriptive qualitative research. This research was chosen because it is to present data systematically, factually, and accurately about the facts in the field. The data collection method used was a questionnaire. The parameters obtained are based on a study that is defined as an investigation conducted on the utilisation of the performance of the State Civil Apparatus according to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia number 38 of 2018. The data analysis technique used in this study is the qualitative data analysis of Miles and Hubermen models. Based on the results of the study, it can be concluded that: the results of the interpretation of the questionnaire that has been distributed to 20 ASN Secretary of Malang Regency were found that the performance in the research location was still excellent. Employee career development can still be said to be useful where effective career development will improve and enhance the effectiveness of the work carried out by employees in order to be able to provide the best contribution in realising organisational goals.